Stabilitas Paving Block Menggunakan Plastik PET (Polyethylene Terephthalate) Dengan Tambahan Serat Bendrat - Maghfira, Maghfira; Mustakim, Mustakim; Muis, Abd (Jurnal Karajata Engineering, 2024)
Plastic waste is one of the most complex problems especially in the Parepare region. Recycling of plastic waste is rare, so the number of garbage piles increases annually. Paving block made from PET plastic waste is one form of effort to reduce the accumulation of plastic waste. The non biodegradable properties of polyethylene cause the plastic aggregate in paving block not to be easily crushed, so it can keep paving block density over a long period of time. The purpose of this study was to determine the stability and compressive strength of paving blocks made of plastic with a variation of 50% PET, 75% PET and 100% PET with bendrat wire fiber, and to find out what the proportion of plastic and sand is in the paving block mixture, which results in optimal compressive strength. The method used is the experimental trial and error method, by experimenting directly in the laboratory. The experiment in question is to make comparisons of the variables studied, so as to produce conclusions that are correlated with the variables studied. From several variations of the planned pet percentage, only 1 variation has stability, namely the 50% PET variant, and the most optimal proportion of plastic and sand is found at 50% PET. The compressive strength obtained is 14.72 MPa for the cube test object and for the paving block specimen it has a compressive strength of 10.16 MPa.